Afrotropical flower flies (Diptera: Syrphidae). A new genus and species from Kenya, with a review of the melanostomine group of genera - Thompson, F. Christian; Skevington, Jeffrey H. (Zootaxa, 2014)
A new genus and species of flower flies (Diptera: Syrphidae: Syrphinae: Syrphini) are described from central Africa (Kenya & Uganda), Afrostoma quadripunctatum. A key to the Afrotropical genera of the subfamily Syrphinae is given. A review of the melanostomine [Bacchini] genera and subgenera is provided along with a key to them. Phylogenetic placement of Afrostoma is included based on mitochondrial cytochrome c oxidase subunit I (COI) data.